Academic identity, confidence and belonging: The role of contextualised admissions and foundation years in higher education. (8th March 2019) - O'Sullivan, Katriona; Bird, Niamh; Robson, James; Winters, Niall
Abstract : This article presents a cross‐national exploration of responses to widening participation (WP), with a specific focus on the provision of foundation year (FY) programmes and the use of contextualised admissions (CA) in selective Irish and UK institutions. There remains a dearth of research on these routes, with little understanding of the characteristics of students who utilise them, of why students use these routes and little knowledge of their effect on students' experiences in university and their overall sense of belonging. A year‐long longitudinal comparative case study design examined three alternative entry routes in two selective higher education institutions (HEIs) in England and Ireland: a well‐established FY; a newly formed FY; and a CA pathway. Data were collected through a mixed‐method approach. Questionnaires and in‐depth focus groups were employed at fixed points with participating students in each route. Results indicated that FY students had lower levels of familial educational history and parental occupation. FY students' sense of belonging significantly increased over the year, with students reporting increased confidence and sense of belonging due to the relationships established during the FY. CA students' sense of belonging remained the same, with students reporting feeling different and isolated. Results indicate that while students utilising FYs may be 'more disadvantaged' than CA students, their experiences helped establish a sense of belonging; illustrating the need for diverse WP routes catering to a wide range of needs. Results highlight the importance of providing opportunities to develop social and bridging social capital for all non‐traditional students.